PENGARUH LITERASI KEUANGAN, PERENCANAAN KEUANGAN DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN PADA IBU RUMAH TANGGA DI DESA BANGAK - Anis Setianingsih; Heny Kurnianingsih (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the influence of financial literacy, financial planning and lifestyle on planning the needs of housewives in Bangak Village. The population used in this research was housewives who lived in Bangak Village. Sampling method by Probability Sampling using Simple Random Sampling technique. Determining the number of respondents at 95 using the Slovin formula. The results of the hypothesis t test in this research show that in particular the financial literacy variable (Xi) has a positive and significant influence on financial management (Y). The financial planning variable (X2) has a negative and insignificant effect on financial management (Y). The lifestyle variable (X3) has a positive and significant effect on financial management (Y). Based on the table from the F test, financial literacy, financial planning and lifestyle simultaneously have a positive and significant effect on financial management among housewives in Bangak Village.